EBCC-13 manifesto: Balancing pros and cons for contralateral prophylactic mastectomy. (March 2023) - Schmidt, Marjanka K.; Kelly, Jennifer E.; Brédart, Anne; Cameron, David A.; de Boniface, Jana; Easton, Douglas F.; Offersen, Birgitte V.; Poulakaki, Fiorita; Rubio, Isabel T.; Sardanelli, Francesco; Schmutzler, Rita; Spanic, Tanja; et al.
Abstract: After a diagnosis of unilateral breast cancer, increasing numbers of patients are requesting contralateral prophylactic mastectomy (CPM), the surgical removal of the healthy breast after diagnosis of unilateral breast cancer. It is important for the community of breast cancer specialists to provide meaningful guidance to women considering CPM. This manifesto discusses the issues and challenges of CPM and provides recommendations to improve oncological, surgical, physical and psychological outcomes for women presenting with unilateral breast cancer: (1) Communicate best available risks in manageable timeframes to prioritise actions; better risk stratification and implementation of risk-assessment tools combining family history, genetic and genomic information, and treatment and prognosis of the first breast cancer are required; (2) Reserve CPM for specific situations; in women not at high risk of contralateral breast cancer (CBC), ipsilateral breast-conserving surgery is the recommended option; (3) Encourage patients at low or intermediate risk of CBC to delay decisions on CPM until treatment for the primary cancer is complete, to focus on treating the existing disease first; (4) Provide patients with personalised information about the risk:benefit balance of CPM in manageable timeframes; (5) Ensure patients have an informed understanding of the competing risks for CBC and that there is a realistic plan for the patient; (6) Ensure patients understand the short- and long-term physical effects of CPM; (7) In patients considering CPM, offer psychological and surgical counselling before surgery; anxiety alone is not an indication for CPM; (8) Eliminate inequality between countries in reimbursement strategies; CPM should be reimbursed if it is considered a reasonable option resulting from multidisciplinary tumour board assessment; (9) Treat breast cancer patients at specialist breast units providing the entire patient-centred pathway. Graphical abstract: Recommendations 1. Communicate the best available risks in manageable timeframes to prioritise actions; better risk stratification and implementation of risk-assessment tools combining family history, genetic and genomic information, and treatment and prognosis of the first breast cancer are required 2. Reserve CPM for specific situations; in women not at high risk of CBC, ipsilateral breast-conserving surgery is the recommended option 3. Encourage patients at low or intermediate risk of CBC to delay decisions on CPM until treatment for the primary cancer is complete, to focus on treating the existing disease first 4. Provide patients with personalised information about the risk:benefit balance of CPM in manageable timeframes 5. Ensure patients have an informed understanding of the competing risks for CBC and that there is a realistic plan for the patient 6. Ensure patients understand the short- and long-term physical effects of CPM 7. In patients considering CPM, offer psychological and surgical counselling before surgery; anxiety alone is not an indication for CPM 8. Eliminate inequality between countries in reimbursement strategies; CPM should be reimbursed if it is considered a reasonable option resulting from multidisciplinary tumour board assessment 9. Treat breast cancer patients at specialist breast units providing the entire patient-centred pathway Image 1 Highlights: Increasingly, patients diagnosed with unilateral breast cancer request CPM. Here, a multidisciplinary panel of breast cancer experts provides guidance on CPM. Patients should be counselled and treated at specialist breast centres. Patients need to understand competing risks for contralateral breast cancer. Patients need personalised information about CPM risk:benefit and a realistic plan.